Multivariable calculus - Stewart, James 1941-; Clegg, Daniel; Watson, Saleem (Boston, MA, USA Cengage, 2021)
"College-level course in multivariable calculus, including partial derivatives, multiple integrals, and vector calculus."--Provided by publisher.
Parametric equations and polar coordinates -- Sequences, series, and power series -- Vectors and the geometry of space -- Vector functions -- Partial derivatives -- Multiple integrals -- Vector calculus -- Appendixes.
Includes index.
Keywords: Calculus